The Effect of Quantum Dots on the Performance of the Solar Cell - Ahmed, Iman Mohsen; Alsaif, Omar Ibrahim; Algwari, Qais Th. (Iraqi Journal for Electrical and Electronic Engineering, 2024)
Quantum dot solar cells are currently the subject of research in the fields of renewable energy, photovoltaics and optoelectronics, due to their advantages which enables them to overcome the limitations of traditional solar cells. The inability of ordinary solar cells to generate charge carriers, which is prevents them from contributing to generate the current in solar cells. This work focuses on modeling and simulating of Quantum Dot Solar Cells based on InAs/GaAs as well as regular type of GaAs p-i-n solar cells and to study the effect of increasing quantum dots layers at the performance of the solar cell. The low energy of the fell photons considers as one of the most difficult problems that must deal with. According to simulation data, the power conversion efficiency increases from (12.515% to 30.94%), current density rises from 16.4047 mA/cm2 for standard solar cell to 39.4775 mA/cm2) using quantum dot techniques (20-layers) compared to traditional type of GaAs solar cell. Additionally, low energy photons’ absorption range edge expanded from (400 to 900 nm) for quantum technique. The results have been modeled and simulated using (SILVACO Software), which proved the power conversion efficiency of InAs/GaAs quantum dot solar cells is significantly higher than traditional (p-i-n) type about (247%).